Evaluasi User Experience Game 2D Bajaj Keliling Menggunakan Metode Game Experience Questionnaire - Nike Joncicilia; Riwinoto Riwinoto; Intan Iqlima (Politeknik Negeri Batam, 2020)
In this digital era, the smartphone game became popular for all people. Even though the number of gamers in Indonesia is increasing, it does not guarantee that every game has a large number of enthusiasts. Every game industry is competing to have a good user experience so that those interested in the game industry always increase. This indicates that user experience in a game is very important to support the success of a game. The Bajaj Keliling game has never done a user experience evaluation before. For the success of the Bajaj Keliling game, it is necessary to evaluate the user experience. After evaluating the user experience in the Bajaj Keliling game, a redesign will be conducted based on the recommendation of the first user experience evaluation, then the results of the redesign of the Bajaj Keliling game will be re-evaluated. The evaluation uses the Game Experience Questionnaire method, while the design process uses the Design Sprint method. After the first analysis, the results showed that the Core Module for the flow component was 2.17 and challenge components was 2.21, and the challenge components on the In-game Module was 2.22, all of these mean values were low and below the median. This shows that the game is easy to play and not too challenging. The solution implemented is to change the stage feature to a level and add a new challenge in the form of a question at the beginning of each level. After the second evaluation, the results on the Core Module for the flow component were 3.17 and challenge components were 3.09, the mean values increased and was above the median. The results of the challenge component in the In-game Module also increased to 2.37, but the mean value was still below the median.